1999
DOI: 10.1016/s0735-1097(99)00466-0
|View full text |Cite
|
Sign up to set email alerts
|

The significance of persistent ST elevation versus early resolution of ST segment elevation after primary PTCA

Abstract: Absence of early ST segment elevation resolution after angiographically successful primary PTCA identifies patients who are less likely to benefit from the early restoration of flow in the IRA, probably because of microvascular damage and subsequently less myocardial salvage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
1
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(113 citation statements)
references
References 28 publications
7
97
1
6
Order By: Relevance
“…12 Investigators reported that persistent ST-segment ele-vation shortly after successful infarct-related artery (IRA) recanalization reflects impairment of microvascular flow. [13][14][15] We therefore hypothesized that the extent of ST-segment resolution can predict LV recovery after reperfused AMI. To test this hypothesis, we examined the relationship between persistent ST-segment elevation shortly after primary stenting for AMI and functional recovery of regional LV function.…”
Section: Introductionmentioning
confidence: 99%
“…12 Investigators reported that persistent ST-segment ele-vation shortly after successful infarct-related artery (IRA) recanalization reflects impairment of microvascular flow. [13][14][15] We therefore hypothesized that the extent of ST-segment resolution can predict LV recovery after reperfused AMI. To test this hypothesis, we examined the relationship between persistent ST-segment elevation shortly after primary stenting for AMI and functional recovery of regional LV function.…”
Section: Introductionmentioning
confidence: 99%
“…U nekim drugim ispitivanjima, veća učestalost hipertenzije je nađena u grupi bolesnika koji su imali ranu kompletnu rezoluciju ST segmneta [21]. Postoje radovi u kojima učestalost hipertenzije nije značajna između grupa sa kompletnom, parcijalnom i odsutnom rezolucijom ST segmenta [22].…”
Section: Broj Faktora Rizikaunclassified
“…U praksi se za ovu procjenu koriste: određivanje Thrombolysis In Myocardial Infarction (TIMI) protoka, određivanje stepena rezolucije ST segmenta, pojava reperfuzionih aritmija te rana pojava maksimalnih vrijednosti srčanih enzima. Iako je TIMI 3 koronarni protok tradicionalno smatran najpouzdanijim surogatom uspješne reperfuzije, pokazano je da je to neadekvatna mjera miokardne perfuzije kod mnogih bolesnika bez obzira kako je perfuzija postignuta [2,3]. Najdostupnije, i u isto vrijeme veoma korisno kliničko sredstvo za određivanje uspjeha reperfuzione terapije nakon STEMI je stepen rezolucije ST segmenta u odnosu na ST segment pri prijemu.…”
Section: Uvodunclassified